Persepsi Dosen Tentang Interprofesional Education (Ipe)Di Universitas Muhammadiyah Surakarta - Sidhik Permana, Rahmat; , Enita Dewi, S.Kep.,Ns.,MN (2016)
The demands of the health care system that increases affect the competence of medical students in understanding the practices in health care , so that the role of the lecturer as facilitator in the process of education has a very important role in the learning process IPE . IPE at UMS is still relatively new and has never been done research on the perception of IPE . The perception of lecturers of the IPE is needed to describe the role of professor as a facilitator in the learning process IPE to improve the competence of medical students in understanding health care practices and be able to form a student to understand the duties and authority of each corresponding profession. Interprofessionl education allows two or more professions to learn with, from and about each other professions to improve cooperation and quality of service. IPE used in colleges to encourage groups of students to work and learn together more effectively. The purpose of this study was to determine the perceptions of teachers about IPE. This research uses descriptive method with a total population sample of 23 respondents. The instrument used was a questionnaire Interdisciplinary Education Perception Scale (IEPs) in which there are four components. Based on statistical analysis showed that the perception of teachers about IPE components faculty competence and autonomy berpersepsi good (87%), components for better collaboration berpersepsi lecturers (52.2%), the perception of the components work together real good berpersepsi lecturers (95.7% ), and component understanding of other professions lecturer berpersepsi well (100%). The conclusion of this study is the average lecturer has a good perception of the IPE in UMS. Based on these results expected UMS nursing courses and other courses within the scope of the study can better integrate health of the IPE.